IMPLEMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER PADA SISWA: SD NEGERI JERUK SOKSOK 1 - JAROT JAROT (Dewan Pendidikan Bondowoso, 2022)
Numbered Heads Together is a learning method with a numbering system that prioritizes interaction patterns between students who are formed in groups of students and always work cooperatively in answering questions given by the teacher. understanding NHT is a type of structural approach cooperative learning that provides opportunities for students to share ideas and consider the most appropriate answers. In addition, Numbered Heads Together also encourages students to increase their cooperation. This model can be used for all subjects and all levels of learners. This research is entitled